Influence of Ageing on Sealability of Elastomeric O‐Rings. Issue 1 (June 2017) - Kömmling, Anja; Jaunich, Matthias; Pourmand, Payam; Wolff, Dietmar; Gedde, Ulf W.
Summary: At BAM, which is the federal institute for materials research and testing in Germany, it is one of our tasks to evaluate the safety of casks designed for transport and/or storage of radioactive material. This includes the assessment of the service lifetime of elastomeric seals that are part of the container lid system with regard to the requirements for long‐term safety (40 years and more) of the containers. Therefore, we started an accelerated ageing programme with selected rubbers often used for seals (HNBR, EPDM and FKM) which are aged at four different temperatures (75 °C, 100 °C, 125 °C and 150 °C) up to 1.5 years. In order to assess sealability, O‐rings are aged in compression by 25% (corresponding to the compression during service) between plates as well as in flanges that allow leakage rate measurements. For comparison, uncompressed O‐rings are aged as well. Further methods characterising seal performance are compression stress relaxation (CSR) reflecting the loss of sealing force of a compressed seal over time, and compression set (CS) which represents the recovery behaviour of a seal after release from compression. Additionally, hardness is measured for information about the change of mechanical properties. The experimental results indicate that while hardness, CSR and CS show considerable degradation effects, the leakage rate stays relatively constant or even decreases until shrinkage combined with the loss of resilience of the aged seal leads to leakage. This demonstrates that static leakage rate, which is the only available direct seal performance criterion, has only limited sensitivity towards the degradation of the seal material. CS data is extrapolated using time‐temperature shifts and Arrhenius graphs. An exemplary CS of 50% would be reached after approx. 1.2, 17 and 29 years at 60 °C for HNBR, EPDM and FKM respectively.